الطاقة النفسیة وعلاقتھا بمستوى أداء مھارة الإرسال وترتیب بعض الفرق المشاركة في بطولة الجامعة التقنیة الوسطى بكرة الطائرة للسیدات - لمى سمير سمير; غيداء محمد محمد; شيرين لعيبي لعيبي (الرياضة المعاصرة, 2016)
The research problem is that most of teams training lack of attention to the psychological aspect in general, and psychic energy in particular besides that there are failure by some of the teams in level of transmitter skill, This in turn led to the loss of a chance to win the game and occupation delayed mattresses compared with the rest of the teams. So that, the researchers seem to make a study in which to knowledge of psychological energy level and the level of transmitter skill for the top three teams in the champion, also knowing the relation between psychological energy and level of transmitter skill and teams arrangement . The researcher used descriptive method by the style of connectivity relations on a sample consist of (36) player to represent (3) teams that take the top three positions in the champion of Central Technical University of women volleyball The researchers relied on psychic energy scale and analysis transmitter skill during the game to find out the results, and on the spot of the results and use of appropriate statistical methods, they reached a number of conclusions, the most important one is that the level of psychological energy of the team of Applied Arts Institute/Al-Zaafaraniya was good, while there is a weakness in psychological energy level of the teams of (Management Institute/Al-Rusafa - Technical Management Institute/Al-Zaafaraniya) , as well as there is a significant correlation relationship between psychological energy and each of